2019
DOI: 10.3390/ijerph16183499
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Evaluation and Spatial Difference Analysis of Regional Ecological Carrying Capacity: A Case Study of the Yangtze River Urban Agglomeration

Abstract: Ecological carrying capacity is an important factor of sustainable development for cities, and a critical part of achieving the coordinated development of the social economic and ecological environment for urban agglomerations. In order to evaluate the regional ecological carrying capacity and provide a basis for decision-making for regional sustainable development, this paper constructs an ecological carrying capacity model for the urban agglomeration from two dimensions: ecological carrying elastic force and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 30 publications
(29 reference statements)
1
28
0
Order By: Relevance
“…The YRUA covers 8 cities along the Yangtze River in Jiangsu province: Nanjing, Zhenjiang, Changzhou, Wuxi, Suzhou, Yangzhou, Taizhou, and Nantong. The 51 000‐km 2 area is home to nearly 50 million people, and it has an economic scale of 6 trillion yuan and a per capita gross domestic product (GDP) of more than 1 210 000 yuan; however, the industrial development model of high energy consumption, high pollution, high emissions, and low returns has not fundamentally changed (Xia and Zhu 2018; Wang et al 2019). The high demand for resources and investment in social and economic development has caused problems such as regional ecological damage and environmental pollution (Zhang and Wen 2008).…”
Section: Methodsmentioning
confidence: 99%
“…The YRUA covers 8 cities along the Yangtze River in Jiangsu province: Nanjing, Zhenjiang, Changzhou, Wuxi, Suzhou, Yangzhou, Taizhou, and Nantong. The 51 000‐km 2 area is home to nearly 50 million people, and it has an economic scale of 6 trillion yuan and a per capita gross domestic product (GDP) of more than 1 210 000 yuan; however, the industrial development model of high energy consumption, high pollution, high emissions, and low returns has not fundamentally changed (Xia and Zhu 2018; Wang et al 2019). The high demand for resources and investment in social and economic development has caused problems such as regional ecological damage and environmental pollution (Zhang and Wen 2008).…”
Section: Methodsmentioning
confidence: 99%
“…Scholars generally believe that it objectively reflects the self-regulation ability of the ecosystem and the ability to maintain ecological balance [13], and the endurance of an external disturbance, especially human activities [14]. It is seen as a comprehensive reflection of the material composition and structure of the ecological environment system [15]. In urban artificial ecosystems, there are energy sources, resource inputs, and waste discharges, which require urban ecosystems to provide support and adjust to urban development services.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In China, more and more scholars pay attention to the extension of environmental carrying capacity in different fields and have achieved some results. For example, many studies in China have found the ecological carrying capacity in various aspects [21][22][23]; however, there is limited literature that focuses on the evaluation of airport environmental carrying capacity.…”
Section: Environmental Carrying Capacity (Ecc)mentioning
confidence: 99%